Aberrant TGF-β1 signaling activation by MAF underlies pathological lens growth in high myopia - Zhu, Xiangjia; Du, Yu; Li, Dan; Xu, Jie; Wu, Qingfeng; He, Wenwen; Zhang, Keke; Zhu, Jie; Guo, Linying; Qi, Ming; Liu, Ailin; Qi, Jiao; et al. (Nature communications, 2021)
High myopia is a leading cause of blindness worldwide. Myopia progression may lead to pathological changes of lens and affect the outcome of lens surgery, but the underlying mechanism remains unclear. Here, we find an increased lens size in highly myopic eyes associated with up-regulation of β/γ-crystallin expressions. Similar findings are replicated in two independent mouse models of high myopia. Mechanistic studies show that the transcription factor MAF plays an essential role in up-regulating β/γ-crystallins in high myopia, by direct activation of the crystallin gene promoters and by activation of TGF-β1-Smad signaling. Our results establish lens morphological and molecular changes as a characteristic feature of high myopia, and point to the dysregulation of the MAF-TGF-β1-crystallin axis as an underlying mechanism, providing an insight for therapeutic interventions. High myopia is associated with lens changes, but the underlying mechanisms are unclear. Here, the authors show increased equatorial diameter of the lens in subjects affected by high myopia, and find that these changes are associated with an increase in crystallin expression driven by the transcription factor MAF and TGF-β1 signaling.